Efficient swing control of an overhead crane with simultaneous payload hoisting and external disturbances - Mohamed, Zaharuddin; Jaafar, Hazriq Izzuan; Ramli, Liyana; M. Lazim, Izzuddin; Efe, Mehmet Önder (Elsevier Ltd., 2020)
The effects of time varying parameters and external disturbances on a flexible system may badly degrade the control performance resulting in excessive induced vibrations/oscillations. For an overhead crane, the oscillation can be even worse when both factors occur simultaneously. This paper proposes a novel swing control approach for an underactuated overhead crane having payload hoisting and external disturbance simultaneously. The proposed scheme is designed based on a predictive unity magnitude shaper and an adaptive feedback control which efficiently suppress payload swing to handle both effects. Furthermore, the control parameters can be updated online in real time to progressively suppress the payload swing. To evaluate the effectiveness of the proposed method, experiments are carried out with a simultaneous payload hoisting and external disturbances including a non-zero initial condition, persistent disturbance (wind) and instant disturbance. The developed controller achieves higher robustness under all testing conditions with significant swing reductions of at least 45% and 69% in the overall and residual swing responses, respectively over a comparative control method. It is envisaged that the proposed method can be very beneficial as an anti-swing controller for various cranes under the influence of disturbance and hoisting simultaneously.